The management of opera an international comparative study - Agid, Philippe 1938-; Tarondeau, Jean-Claude (Palgrave Macmillan, 2010)
This book presents the current and future issues facing opera houses and opera companies. Problems in different environments need different solutions. In particular, it opposes the American method of managing cultural institutions, preferring a European one where public support and funds plays a major role